Seva Sadan speaks : golden jubilee, Poona Seva Sadan Society, Nagpur Branch, Nagpur - Gokhale, A. R.; Niyogi, M. B.; Kulkarni, Anant Ramchandra, 1897- (Poona Seva Sadan Society, Nagpur Branch, 1977)
Contributed articles on the activities, 1927-1976, of a women's society at Nagpur.